Two new species of Nemoura (Plecoptera: Nemouridae) from Henan, China - Li, Weihai; Yang, Ding (Zootaxa, 2007)
The genus Nemoura Latreille belongs to the subfamily Nemourinae and has more than 100 known species from the Holarctic and Oriental Regions. The species of Nemoura from China were studied mainly by Chu (1928), Wu (1938, 1962, 1973), Zhu & Yang (2003) and Li & Yang (2006). Currently, 24 species are known to occur from China